PENGARUH KONDISI LINGKUNGAN TERHADAP KARAKTERISTIK SEMUT DAN POLA SARANG DI PEMATANG SAWAH - Abdullah, Tamrin; Prihatin; Ahdin Gassa1; Sri Nur Aminah1; Kusdini Kusdini; Nurul Wiridannisaa (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2025)
Rice fields are farmlands that are bounded and surrounded by bunds and channels to retain and drain water. This is done in a way that allows for the cultivation of rice plants and the need for inundation during the rice growing period. In areas designated for rice cultivation, bunds can be utilised to plant various types of cultivated plants. This study aims to determine ant species and natural nesting patterns of ants in rice paddy fields. This research was conducted in Labuanpatu Neighbourhood, Mappadaelo Village, Tanasitolo District, Wajo Regency. Sample identification of ant species was conducted at the Plant Pest Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Hasanuddin University. Data collection was conducted by direct observation of natural nests, ant identification, and ant population counts. The results showed that the identification of ants in three different locations of the bund, found 6 ant species and 3 different subfamilies, namely subfamily Formicinae (Oecophyilla sp., Anoplolepis sp., and Componatus sp.), subfamily Myrmicinae (Solenopsis sp. and Tetramorium sp.) and subfamily Dolicodolinae (Tapinoma sp.). Ant species diversity and the number of ant individuals present are strongly influenced by environmental and habitat conditions. Field observations show that as human disturbance increases, ant diversity also decreases. The formation of natural ant nests depends on the availability of suitable components. These include green leaves, soil, weathered logs or tree branches.